Prevalence of Pediculosis in Some Primary Schools in Diyala Province, Iraq: Prevalensi Pedikulosis di Beberapa Sekolah Dasar di Provinsi Diyala, Irak - Abed, Noora Dhyaaldain (Academia Open, 2024)
Background:Pediculosis (human head lice) infestation is aglobal problem among primary schools.Aims: This study has been conducted to investigate the prevalence of head lice among some primary schools in Diyala province. Methodology and Results: The study samples were randomly collected from the city center and villages, during the period from October/2022 to February/2023. This study examined 1579 pupils to detect pediculosis. The results have revealed 234 infections among the school students which represents 14.819% of the total examined sample. The infections among females were higher than males (217) females were infected which represents 92.735% of the total infections. Moreover, the study found that the proportion of pediculosis in rural areas was higher than in urban,60.256% and 39.743% respectively. The study has also shown the highest rate of infection among females in ages 10-14 years 39.316%, compared with other groups, Moreover, the study has shown the relationship between the mother’s education level and pediculosis. The percentage of infection among students who have mothers without university degrees was 83.333% while those who have mothers with university degrees were 16.666%. The study has also pointed to the significant effect of family size on infection percentages. A high percentage was recognized among those who live in big families,66.239%. Conclusion, significance, and impact of study: Infection is prevalent among pupils, and risk factors play an important role in this situation which requires that controlling the infection and treating infected pupils be given the utmost importance to increase awareness. Highlights: Prevalence: 14.8% of students infected, higher in females and rural areas. Risk Factors: Low maternal education and large family size increase infection. Action: Control measures and awareness programs are urgently needed. Keywords: Pediculosis, Head lice, Nits, Pediculus humanus capitis